Argumentação e aprendizagem de matemática: uma experiência de geometria no ensino fundamental - Rigo, Franciele Simionato (2021)
National assessments, such as ENEM and Prova Brasil, show the difficulties that students have in organizing ideas to prove mathematical results and the consequent repercussion in the ability to solve problems, as it is necessary to state their own reasoning and manifest them coherently. In this sense, this research aims to analyze the relation between argumentation and mathematics learning processes present in an experience of teaching geometry at the Basic School. Toulmin's model and Ausubel's Theory of Meaningful Learning were adopted as a basis for argumentation and learning issues, respectively. A sequence of teaching Activities on regular polygons was elaborated and applied remotely, in classes of the eighth grade of elementary school in a public school. The records were made with audio recordings and notes in the logbook. The rendering of the meanings of the students' manifestations, performed with the support of the Content Analysis methodology, features the research as qualitative, descriptive and analytical. The analysis of the students' manifestations showed that the discussion processes, for more elementary that they can be, produce meanings for concepts and hypothesis, besides practicing mathematical language, makes learning meaningful.